The multifaceted phenotypic and genotypic spectrum of type-IV-collagen-related nephropathy—A human genetics department experience - Ćomić, Jasmina; Riedhammer, Korbinian M.; Günthner, Roman; Schaaf, Christian W.; Richthammer, Patrick; Simmendinger, Hannes; Kieffer, Donald; Berutti, Riccardo; Tasic, Velibor; Abazi-Emini, Nora; Nushi-Stavileci, Valbona; Putnik, Jovana; et al. (Frontiers in Medicine, 2022)
Disease-causing variants in COL4A3-5 are associated with type-IV-collagen-related nephropathy, a genetically and phenotypically multifaceted disorder comprising Alport syndrome (AS) and thin basement membrane nephropathy (TBMN) and autosomal, X-linked and a proposed digenic inheritance. Initial symptoms of individuals with AS are microscopic hematuria followed by proteinuria leading to kidney failure (90% on dialysis < age 40 years). In contrast, individuals with TBMN, an outdated histology-derived term, present with microscopic hematuria, only some of them develop kidney failure (> 50 years of age). An early diagnosis of type-IV-collagen-related nephropathy is essential for optimized therapy and slowing of the disease. Sixty index cases, in whom exome sequencing had been performed and with disease-causing variant(s) in COL4A3-5, were evaluated concerning their clinical tentative diagnosis and their genotype. Of 60 reevaluated individuals with type-IV-collagen-related nephropathy, 72% had AS, 23% TBMN and 5% focal segmental glomerulosclerosis (FSGS) as clinical tentative diagnosis. The FSGS cases had to be re-classified as having type-IV-collagen-related nephropathy. 12% of cases had AS as clinical tentative diagnosis and a monoallelic disease-causing variant in COL4A3/4 but could not be classified as autosomal dominant AS because of limited or conflicting clinical data. This study illustrates the complex clinical and genetic picture of individuals with a type IV-collagen-related nephropathy indicating the need of a refined nomenclature and the more interdisciplinary teamwork of clinicians and geneticist as the key to optimized patient care.